1997
DOI: 10.1161/01.atv.17.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17β-Estradiol on Plasma Lipids and LDL Oxidation in Postmenopausal Women With Type II Diabetes Mellitus

Abstract: In type II diabetes mellitus the altered hormonal state after menopause may represent an additional cardiovascular risk factor. Estrogen replacement therapy (ERT) is associated with a decreased cardiovascular risk, at least in nondiabetic postmenopausal women. We studied the effect of ERT on plasma lipids and lipoproteins and on LDL oxidation in 40 postmenopausal women with type II diabetes but with minimal vascular complications in a randomized placebo-controlled trial. Twenty patients were treated orally wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…Many studies support the role of estrogens in the primary and secondary prevention of CHD among women (38,39), particularly in normalizing blood lipids or inducing endothelium-dependent vasodilation stimulating nitric oxide synthetase (40 -42). It has recently been demonstrated in premenopausal diabetic women that there is a decreased estrogeninducing endothelium-dependent vasodilation (43), which can explain the increased risk of cardiovascular mortality in diabetic women.…”
Section: Results -As Shown Inmentioning
confidence: 99%
“…Many studies support the role of estrogens in the primary and secondary prevention of CHD among women (38,39), particularly in normalizing blood lipids or inducing endothelium-dependent vasodilation stimulating nitric oxide synthetase (40 -42). It has recently been demonstrated in premenopausal diabetic women that there is a decreased estrogeninducing endothelium-dependent vasodilation (43), which can explain the increased risk of cardiovascular mortality in diabetic women.…”
Section: Results -As Shown Inmentioning
confidence: 99%
“…The addition of estrogens to a system of LDL oxidation mediated by copper showed an increase in the initiation time of LDL oxidation 26 . Several studies have shown the effect of the administration of estrogens on human LDL oxidation [50][51][52] . Therefore, the reduced concentration of estrogens could partially explain the increase in lipid peroxidation in postmenopausal women observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…42,48,50 Briefly, from each subject 3.5 mL of frozen plasma, stored at Ϫ80°C, was rapidly thawed and used for isolation of LDL by ultracentrifugation at 4°C in the presence of 10 mol/L EDTA. To minimize the time between isolation and oxidation, the LDL was not dialyzed.…”
Section: Preparation and Oxidation Of Ldlmentioning
confidence: 99%
“…By omitting dialysis we obtained a more stable LDL preparation, which can be stored in the dark at 4°C under nitrogen for several days without effect on resistance time and propagation rate. 48,50 This improves the precision of the method, because each LDL preparation can be oxidized consecutively in triplicate. In a representative experiment, lag time was 90Ϯ2 minutes at 1 hour after LDL isolation in a LDL preparation that had not been dialyzed; 24 hours after LDL isolation, lag time was 91Ϯ3 minutes (nϭ3).…”
Section: Preparation and Oxidation Of Ldlmentioning
confidence: 99%
See 1 more Smart Citation